Optical coherence tomography angiography and Humphrey field analyser for macular capillary non-perfusion evaluation in branch retinal vein occlusion - Hiroko Terashima (Nature Portfolio, 2021)
Abstract We non-invasively evaluated macular non-perfused areas (m-NPAs) of branch retinal vein occlusion (BRVO) using optical coherence tomography (OCT) angiography and the Humphrey visual field analyser 10-2 programme (HFA 10-2). We enrolled 30 patients (30 eyes) with macular oedema secondary to BRVO. OCT angiography was used to photograph the macula at 6 × 6-mm; sizes of m-NPAs in the superficial capillary plexus (SCP) and deep capillary plexus (DCP) were measured in four areas. For HFA 10-2, we divided the actual measurement threshold of 68 points into four areas and calculated the mean central visual field sensitivity (CVFS). The correlation between the mean m-NPA and mean CVFS (dB) in each area was examined. There was a strong correlation between the m-NPA of each region detected in SCP and DCP, and the mean CVFS of each corresponding area (SCP: r = − 0.83, r = − 0.64, r = − 0.73, and r = − 0.79; DCP: r = − 0.82, r = − 0.71, r = − 0.71, and r = − 0.70), p values were < 0.001 for all. m-NPAs were associated with decreased visual field sensitivity in BRVO. Non-invasive m-NPA evaluation was possible using OCT angiography and HFA 10-2.